The Robustness of Quadratic Voting - Weyl, E. Glen (via Public Choice, 2016)
Lalley and Weyl (2016) propose a mechanism for binary collective decisions, Quadratic Voting, and prove its approximate efficiency in large populations in a stylized environment. They motivate their proposal substantially based on its greater robustness when compared with pre-existing efficient collective decision mechanisms. However these suggestions are based purely on discussion of structural properties of the mechanism. In this paper I study these robustness properties quantitatively in an equilibrium model. Given the mathematical challenges with establishing results on QV fully formally, my analysis relies on a number of structural conjectures that have been proven in analogous settings in the literature, but in the models I consider here. While most of the factors I study reduce the efficiency of QV to some extent, it is reasonably robust to all of them and quite robustly outperforms one-person-one-vote. Collusion and fraud, except on a very large scale, are deterred either by unilateral deviation incentives or by the reactions of non-participants to the possibility of their occurring. I am only able to study aggregate uncertainty for particular parametric distributions, but using the most canonical structures in the literature I find that such uncertainty reduces limiting efficiency, but never by a large magnitude. Voter mistakes or non-instrumental motivations for voting, so long as they are uncorrelated with values, may either improve or harm efficiency depending on the setting. These findings contrasts with existing (approximately) efficient mechanisms, all of which are highly sensitive to at least one of these factors.